Performance of Different Immobilized Lipases in the Syntheses of Short- and Long-Chain Carboxylic Acid Esters by Esterification Reactions in Organic Media - Lionete De Lima; Adriano Mendes; Roberto Fernandez-Lafuente; Paulo Tardioli; Raquel Giordano (Molecules, 2018)
Short-chain alkyl esters and sugar esters are widely used in the food, pharmaceutical and cosmetic industries due to their flavor and emulsifying characteristics, respectively. Both compounds can be synthesized via biocatalysis using lipases. This work aims to compare the performance of commercial lipases covalently attached to dry acrylic beads functionalized with oxirane groups (lipases from Candida antarctica type B—IMMCALB-T2-350, Pseudomonas fluorescens—IMMAPF-T2-150, and Thermomyces lanuginosus—IMMTLL-T2-150) and a home-made biocatalyst (lipase from Pseudomonas fluorescens adsorbed onto silica coated with octyl groups, named PFL-octyl-silica) in the syntheses of short- and long-chain carboxylic acid esters. Esters with flavor properties were synthetized by esterification of acetic and butyl acids with several alcohols (e.g., ethanol, 1-butanol, 1-hexanol, and isoamyl alcohol), and sugar esters were synthetized by esterification of oleic and lauric acids with fructose and lactose. All biocatalysts showed similar performance in the syntheses of short-chain alkyl esters, with conversions ranging from 88.9 to 98.4%. However, in the syntheses of sugar esters the performance of PFL-octyl-silica was almost always lower than the commercial IMMCALB-T2-350, whose conversion was up to 96% in the synthesis of fructose oleate. Both biocatalysts showed high operational stability in organic media, thus having great potential for biotransformations.